2013
DOI: 10.1007/978-1-4614-7385-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations of Random Differential Equations with Bounded Noise

Abstract: In random differential equations with bounded noise minimal forward invariant (MFI) sets play a central role since they support stationary measures. We study the stability and possible bifurcations of MFI sets. In dimensions 1 and 2 we classify all minimal forward invariant sets and their codimension one bifurcations in bounded noise random differential equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…In [10] the authors showed that the boundary of an MFI set consists of solutions of the extremal vector fields defined by the bounded noise differential equations. Observe that for ε = 0, (8) reads θ̇ = 1 and truer¯˙=0 and its right hand varies continuously with ε.…”
Section: Random Perturbations Of a Planar Hopf-andronov Bifurcationmentioning
confidence: 99%
See 2 more Smart Citations
“…In [10] the authors showed that the boundary of an MFI set consists of solutions of the extremal vector fields defined by the bounded noise differential equations. Observe that for ε = 0, (8) reads θ̇ = 1 and truer¯˙=0 and its right hand varies continuously with ε.…”
Section: Random Perturbations Of a Planar Hopf-andronov Bifurcationmentioning
confidence: 99%
“…We adopt from [10] the following assumptions on (1) and its flow: H1 . The set Δ is a closed disk with smooth boundary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that asymmetric division and variable rate models are both examples of perturbations by bounded noise (see [11, 12, 27]). It is known that random differential equations with bounded noise may undergo discontinuous bifurcations of their minimal forward invariant (MFI) sets.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that random differential equations with bounded noise may undergo discontinuous bifurcations of their minimal forward invariant (MFI) sets. MFI sets are the bounded noise analogue of attractors [12]. Namely, if there is a topological change in the collection of MFI sets, this change must be discontinuous (with respect to the Hausdorff metric on sets) [14].…”
Section: Introductionmentioning
confidence: 99%